Negative Interest Rates: Taking Stock of the Experience So Far - Marques, Luís Brandão (Washington, D.C International Monetary Fund (IMF), 2021)
This paper focuses on negative interest rate policies and covers a broad range of its effects, with a detailed discussion of findings in the academic literature and of broader country experiences (IMF page)
Executive Summary -- Glossary -- Introduction -- 1. Conceptual Issues -- 2. Overview of Empirical and Quantitative Evidence -- 3. Implementation Issues -- 4. Conclusion
Includes bibliographical references (P. 63-76)
Keywords: Banks and Banking; BANKS; MONETARY POLICY; INTEREST RATES